1900 N.Y. Laws 458-59 - (:unkn) unknown (My University, 1900)
Ch. 222, § 1: Prohibited manufacturing or selling a slungshot, billy, sandclub or metal knuckles, and prohibited selling a firearm to a minor in any city or incorporated village without written consent of police magistrate. Exempted any officer of the United States or peace officer when necessary and proper to discharge official duties.
Keywords: TRANSFER - MINORS; TRANSFER, MANUFACTURE & POSSESSION